2019
DOI: 10.1177/0023830919884089
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Word-level Prominence in Free Word Order Language Discourse

Abstract: This study examines the contribution of constituent order, prosody, and information structure to the perception of word-level prominence in Russian, a free word order language. Prominence perception is investigated through the analysis of prominence ratings of nominal words in two published narrative texts. Word-level perceived prominence ratings were obtained from linguistically naïve native speakers of Russian in two tasks: a silent prominence rating task of the read text passages, and an auditory prominence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…In English, and other intonation languages, the prosodically prominent element and the focus in an utterance usually align (Büring, 2009; Calhoun, 2010; Gussenhoven, 2004; Ladd, 2008). However, this is not always the case, and despite the wealth of research in this area, it is not yet clear what cues affect listeners’ perception of prosodic prominence, nor their interpretation of where the focus is in an utterance—though the research that has been done in this area indicates these interact in complex ways (Cole, 2015; Cole, Mo, & Hasegawa-Johnson, 2010; Kember, Choi, Yu, & Cutler, this issue; Luchkina & Cole, this issue; Luchkina, Puri, Jyoti, & Cole, 2015; Vainio & Järvikivi, 2006). This paper investigates prosodic prominence perception and focus interpretation through two sets of parallel experiments in the unrelated languages Samoan and English.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In English, and other intonation languages, the prosodically prominent element and the focus in an utterance usually align (Büring, 2009; Calhoun, 2010; Gussenhoven, 2004; Ladd, 2008). However, this is not always the case, and despite the wealth of research in this area, it is not yet clear what cues affect listeners’ perception of prosodic prominence, nor their interpretation of where the focus is in an utterance—though the research that has been done in this area indicates these interact in complex ways (Cole, 2015; Cole, Mo, & Hasegawa-Johnson, 2010; Kember, Choi, Yu, & Cutler, this issue; Luchkina & Cole, this issue; Luchkina, Puri, Jyoti, & Cole, 2015; Vainio & Järvikivi, 2006). This paper investigates prosodic prominence perception and focus interpretation through two sets of parallel experiments in the unrelated languages Samoan and English.…”
Section: Introductionmentioning
confidence: 99%
“…Bishop (2012) has shown that a context cueing a narrow focus reading on an object (as in (3b)) raises the perceived prominence of the accented word, compared to a broad focus reading (see also Bishop, 2017; Turnbull, Royer, Ito & Speer, 2017). In languages including Finnish, Hindi, and Russian, which make much greater use of word ordering to signal focus/informativeness, it has been shown that words which are placed in syntactic focus positions are perceived as more prosodically prominent, controlling for acoustic prominence (Luchkina & Cole, this issue; Luchkina et al, 2015; Vainio & Järvikivi, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, structural top-down expectations generated from native language prosodic structure drive prosodic structure building if the relevant cues are present in the signal. Likewise, if a language prefers a particular syntactic position for focused constituents, listeners are more likely to interpret the word in this focus position as being the most prominent, rather than a word in a canonical sentence position, as shown in this issue for a Samoan-English comparison and for Russian (Calhoun et al, this issue; Luchkina & Cole, this issue).…”
Section: Introductionmentioning
confidence: 94%
“…These structural positions can both attract and express prominence, guiding attention towards important elements: In languages with a fixed stress system, as for instance Finnish (Karvonen, 2005), Estonian (Lehiste, 1960), or Hungarian (Varga, 2002), the stressed syllable always appears in a fixed position in the word, such that listeners attend to this position. Likewise, in languages with fixed syntactic positions to express focus, these structural positions, such as pre-verbal or phrase final, are inherently prominent, as reflected in prominence judgments in two papers in this issue (Calhoun et al, this issue; Luchkina & Cole, this issue). This type of prominence is driven by expectations about prosodic structure predicted by the grammar of the language.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation